A study of childhood attendance at emergency departments in the West Midlands region. Issue 5 (20th April 2006) - Downing, A; Rudge, G
Abstract : Introduction: Research into childhood attendance at EDs in the UK has focused mainly on injury rather than medical conditions and studies have been relatively small. This study looks at all types of ED attendance by children across a large population. Data and methods: Routine data on all new attendances by children under 16 years were available for 12 EDs in the West Midlands (period: 1 April 2002 to 31 March 2004, 365 695 records). The data were split into four age groups (<1, 1–4, 5–9, and 10–15 years). Results: Injury related conditions increased with age (with the exception of head injury). Respiratory and gastrointestinal were the most common medical conditions decreased with age. 11.5% of children were admitted to hospital and this varied from 8.2% (10–15 years) to 24.2% (<1 year). Conclusions: This study has shown substantial variations in ED attendance by age and has given an insight into the variation among hospitals. This is the largest study of childhood ED attendance undertaken in the UK, and it is hoped that the questions raised will prompt more research in this field.